The FIR Filter Design By Using Window Parameters Calculated With GA - Kaya, Turgay; Ince, Melih Cevdet (Ieee, 2010)
In this study, digital filter design was realized helping window functions that their parameter values were calculated using GA. First in the study, the Kaiser window function parameters used many application was found with GA. This values obtained were used in FIR filter design and filter coefficient values which provide desired conditions were calculated. The amplitude responses obtained from available commands and filter amplitude response according to FIR filter coefficient values founded with programme were compared and plotted. The results have shown that the improved programme has been successful. Besides, this study is to provide decreasing of process steps for calculation of window function coefficients used at different filter conditions.
5th International Conference on Soft Computing, Computing with Words and Perceptions in System Analysis, Decision and Control -- SEP 02-04, 2009 -- Famagusta, CYPRUS